Tożsamość miejsca na przykładzie Warmii – studium przypadku - Sakson, Andrzej (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The aim of the article is to present the role of Polish minority school in interwar period in East Prussia (a part of Germany) in the life of the local population. Sociological field research conducted in two Warmian villages (Purda and Leszno) in the years 1948, 1983, 2005–2006, and 2016 has shown that Polish minority school was and still is an important element of Warmian identity of place
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne